2009
DOI: 10.1097/tp.0b013e3181aed927
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Photophoresis Augments Function of CD4+CD25+FoxP3+ Regulatory T Cells by Triggering Adenosine Production

Abstract: Our data indicate that ECP stimulates the conversion of ATP to adenosine by the ectonucleotiodase CD39, which acts as a novel soluble immunosuppressive reagent mediating immunosuppression of Treg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 21 publications
3
33
0
1
Order By: Relevance
“…In contrast to direct IL-10 inhibition in ECP-treated PBMC, many studies have demonstrated elevated IL-10 either in ECP-untreated DC/ monocytes being cocultured with ECP-exposed cells (12,49,50) or in ECP Tregs, and the requirement for IL-10 was demonstrated in IL-10-deficient mice (10). Furthermore, additional data have suggested that ECP promoted Treg expansion in recipients (51,52). In our view, these results support the hypothesis that ECP may have dual immunomodulatory activity: immunoregulatory activity of ECP-treated apoptotic lymphocytes interacting with ECP-unexposed host cells and possible immunostimulatory activity of directly ECP-exposed monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to direct IL-10 inhibition in ECP-treated PBMC, many studies have demonstrated elevated IL-10 either in ECP-untreated DC/ monocytes being cocultured with ECP-exposed cells (12,49,50) or in ECP Tregs, and the requirement for IL-10 was demonstrated in IL-10-deficient mice (10). Furthermore, additional data have suggested that ECP promoted Treg expansion in recipients (51,52). In our view, these results support the hypothesis that ECP may have dual immunomodulatory activity: immunoregulatory activity of ECP-treated apoptotic lymphocytes interacting with ECP-unexposed host cells and possible immunostimulatory activity of directly ECP-exposed monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Despite its clinical effectiveness, the immunomodulatory mechanisms of ECP are not fully understood. 5 Previous studies proposed triggering of lymphocyte, monocyte and natural killer cell apoptosis, 6 the induction of regulatory T cells (Tregs), [7][8][9] including enhancement of Treg function, 10 modulation of pro-inflammatory cytokines and/ or induction of tolerogenic dendritic cells [11][12][13][14] as potential modes of ECP action. Immature B-cell subsets and levels of B-cell activating factor have been shown to serve as clinical ECPresponse markers.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by the finding that transplant recipients of solid organs or with graftversus-host disease posthematopoietic stem cell transplants treated with ECP exhibited a higher frequency of peripheral T regs (CD41, CD251, FoxP31, and CD692) [12][13][14][15]. More recently, Schmitt et al [16] showed that ECP stimulates the conversion of adenosine triphosphate (ATP) to adenosine, a soluble immunosuppressive mediator of T-cell activation.…”
Section: What Is Ecp and Why Is It An Option In Heart And Lung Transpmentioning
confidence: 88%